Probiotic Treatment Decreases the Number of CD14-Expressing Cells in Porcine Milk Which Correlates with Several Intestinal Immune Parameters in the Piglets - Scharek-Tedin, Lydia; Kreuzer-Redmer, Susanne; Twardziok, Sven Olaf; Siepert, Bianca; Klopfleisch, Robert; Tedin, Karsten; Zentek, Jürgen; Pieper, Robert (Frontiers in Immunology, 2015)
Modulating the mucosal immune system of neonates by probiotic treatment of their mothers is a promising approach which can only be investigated through the use of animal models. Here, we used sows and their piglets to investigate the impact of a bacterial treatment on the sow´s milk and on the neonate piglet intestinal immune system. In previous experiments, feed supplementation of sows with the probiotic Enterococcus faecium NCIMB 10415 during pregnancy and lactation had been shown to affect intestinal microbiota and cytokine expression of the offspring during the suckling and weaning periods. We therefore investigated the composition of the milk from treated sows in comparison to samples from a control group. In treated sows, the amount of lactose increased, and the somatic cell numbers were reduced. In all milk samples, the percentage of cells expressing membranous CD14 (mCD14) was greater than the fractions of immune cells, indicating expression of mCD14 on mammary epithelial cells. However, in the milk of E. faecium-treated sows, mCD14+ cells were reduced. Furthermore, the number of CD14+ milk cells was positively correlated with the percentages of B cells and activated T cells in the ileal MLN of the piglets. This study provides evidence for the expression of mCD14 by the porcine mammary epithelium, and suggests an immunological effect of mCD14+ milk cells on the piglets’ intestinal immune system. Our study further suggests that mCD14+ mammary epithelial cell populations can be modulated by probiotic feed supplementation of the sow. Keywords: pig, Enterococcus faecium, milk, mCD14, intestinal, B cells, T cells.